2020
DOI: 10.3390/ph13120472
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Anxiety-Like Behavior by Helichrysum stoechas (L.) Moench Methanolic Extract through Up-Regulation of ERK Signaling Pathways in Noradrenergic Neurons

Abstract: The long-term use of anxiolytic and antidepressant drugs can cause a plethora of side effects and the use of complementary and alternative medicine, which is generally considered safer than conventional medicine, is consistently increasing. Helichrysum stoechas (L.) Moench methanolic extract (HSE) has shown MAO-A inhibitory properties in previous studies. With the aim of obtaining innovative and safer therapies for mood disorders, this study investigated the potential activity of HSE in the management of anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 52 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…Until now, in vitro studies have shown that this plant has strong antioxidant and anti-inflammatory activities and antimicrobial capacity as well as antiproliferative and antidiabetic effects [ 12 ]. Recently, neuroprotective effects were observed in in vitro and in vivo studies [ 12 , 27 ]. However, the vascular activity of H. stoechas is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, in vitro studies have shown that this plant has strong antioxidant and anti-inflammatory activities and antimicrobial capacity as well as antiproliferative and antidiabetic effects [ 12 ]. Recently, neuroprotective effects were observed in in vitro and in vivo studies [ 12 , 27 ]. However, the vascular activity of H. stoechas is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This rod is placed at a height of about 15 cm from the base of the instrument. The speed of the rod was 16 rpm and the time in which the number of falls of the animal was calculated was 30 s. This test was performed in the baseline (BL) condition and at day 21–28 after surgery [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The longer the animal remained in the center of the box, the less anxious it was. This test was performed in the baseline condition (BL) and on day 21–28 after surgery [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe, for example, the current burden is greater than that from 10 years ago despite the availability of reasonably effective pharmacological and psychological interventions[ 3 ]. Moreover, the World Health Organization in 2008 ranked major depression as the third cause of the disease burden worldwide and predicted that the disease will rank first by 2030[ 4 ]. Furthermore, various studies have shown the impact of depression, anxiety and stress on different systems including the cardiovascular and immune systems[ 5 ].…”
Section: Introductionmentioning
confidence: 99%